Projeto Garabi-Itá: uma sistematização da sua contribuição no processo de conscientização e desenvolvimento sócio-ambiental regional - Silva, Marcela Guimarães e (2005)
This study implies an systematization of the Empreendimento Linha de Transmissão Garabi-Itá: Projeto de Compensação Florestal no Estado do RS . The objectives of the project were twofold: i) to reforest the region of Garabi-Ita in the state of Rio Grande Do Sul planting 280.000 trees with support of 544 rural producers and their families, and ii) to develop environmental awareness and create conditions for the participation of the target population in the project.Through of the quality research carried with the rural producers came to check of objective of the Projeto Garabi-Itá gone to achieve and identify yourself contribution from their environmental development of the rural communities. Nowadays systematization has become an issue of great importance because the society needs to know the project impact in order to continue its financial support, and the target people needs to know the main results of its participation. The systematization of the results leads to generate lessons about development that can be applied in greater contexts with more benefits to the people involved. The project contributed to improve living conditions of rural producers and their families and to strengthen rural communities´ capacities to manage their natural resources from a sustainable perspective, through the participation of the main actors.